The Ubiquitin E3 Ligase Parkin Inhibits Innate Antiviral Immunity Through K48-Linked Polyubiquitination of RIG-I and MDA5 - Bu, Lang; Wang, Huan; Hou, Panpan; Guo, Shuting; He, Miao; Xiao, Jingshu; Li, Ping; Zhong, Yongheng; Jia, Penghui; Cao, Yuanyuan; Liang, Guanzhan; Yang, Chenwei; et al. (Frontiers in Immunology, 2020)
Innate immunity is the first-line defense against antiviral or antimicrobial infection. RIG-I and MDA5, which mediate the recognition of pathogen-derived nucleic acids, are essential for production of type I interferons (IFN). Here, we identified mitochondrion depolarization inducer carbonyl cyanide 3-chlorophenylhydrazone (CCCP) inhibited the response and antiviral activity of type I IFN during viral infection. Furthermore, we found that the PTEN-induced putative kinase 1 (PINK1) and the E3 ubiquitin-protein ligase Parkin mediated mitophagy, thus negatively regulating the activation of RIG-I and MDA5. Parkin directly interacted with and catalyzed the K48-linked polyubiquitination and subsequent degradation of RIG-I and MDA5. Thus, we demonstrate that Parkin limits RLR-triggered innate immunity activation, suggesting Parkin as a potential therapeutic target for the control of viral infection.